The EFEKTIVITAS ANTIBAKTERI DAN ANTIOKSIDAN SABUN FACIAL WASH EKSTRAK ETANOL BIJI LIMUS (Mangifera foetida L) - Vera Nurviana; Luthfi fadillah suharta; Aisyah Shiddiqah Nasir; Hildan Akhrija Jakriyana; Salma Marjani Djahroh (JURNAL KATALISATOR, 2022)
Facial wash preparations are cosmetic products that are widely used routinely by the public. Facial soap is used as an alternative to anti-acne and antioxidant which is known to the public to be more practical and economical. Active substances from herbal ingredients are increasingly being sought by the public with the reason to get results that are effective, natural, and with a high level of safety. Limus seed kernels are known to have good antibacterial activity, one of which is against Staphylococcus aureus bacteria which can cause skin infections. In addition, limus seed kernels are reported to have very strong antioxidant activity. The purpose of this study was to determine the effectiveness of antibacterial and antioxidant facial wash gel. The stages of the research carried out are, extract making (extract obtained by maceration method using ethanol 96%), phytochemical screening, preparation, and evaluation of the preparation. The process of making the preparation was divided into 3 formulas with a ratio of the concentration of ethanol extract of lime seeds in succession. Stock evaluation includes foam level test, homogeneity test, pH test, organoleptic test, antioxidant activity test using the DPPH method and antibacterial testing using the agar diffusion method. The results showed that formula 3 was the best formula with an average inhibition zone of the preparation against Staphylococcus aureus of 16.333 mm (strong) and the antioxidant IC50 value of 2.237 ppm (very strong).